A Review on Performance Analysis and Improvement of Internet of Things Application - Bharti, Ajay Kumar; Negi, Rashmi; Verma, Deepak Kumar (International Journal of Computer Sciences and Engineering, 2019)
Big data and IoT is two different challenging terms in IT industry. Currently, IoT is an emerging technology and is being used various application for development and research. Big Data Stream Computing (BDSC) is an emerging feature for dealing a real-time data streams and providing faster decisions. BDSC is being used in much of the real time IOT applications. The main objective of the work is to review and measure the performance analysis of real-time IoT application data processing using BDSC platform.